Role of the YehD fimbriae in the virulence-associated properties of enteroaggregative Escherichia coli - Soria-Bustos, Jorge; Saitz, Waleska; Medrano, Abraham; Lara-Ochoa, Cristina; Bennis, Zineb; Monteiro-Neto, Valerio; dos Santos, Camilla Itapary; Rodrigues, Josias [UNESP]; Hernandes, Rodrigo T. [UNESP]; Yáñez, Jorge A.; Torres, Javier; Navarro-García, Fernando; et al. (Wiley, 2021)
The interaction of enteroaggregative Escherichia coli (EAEC) strains with the colonic gut mucosa is characterized by the ability of the bacteria to form robust biofilms, to bind mucin, and induce a local inflammatory response. These events are mediated by a repertoire of five different aggregative adherence fimbriae variants (AAF/I-V) typically encoded on virulence plasmids. In this study, we report the production in EAEC strains of a new YehD fimbriae (YDF), which is encoded by the chromosomal gene cluster yehABCD, also present in most E. coli strains. Immuno-labelling of EAEC strain 042 with anti-AAF/II and anti-YDF antibodies demonstrated the presence of both AAF/II and YDF on the bacterial surface. We investigated the role of YDF in cell adherence, biofilm formation, colonization of spinach leaves, and induction of pro-inflammatory cytokines release. To this aim, we constructed yehD deletion mutants in different EAEC backgrounds (strains 17-2, 042, 55989, C1010, 278-1, J7) each harbouring one of the five AAFs. The effect of the YDF mutation was strain dependent and AAF independent as the lack of YDF had a different impact on the phenotypes manifested by the different EAECs tested. Expression of the yehABCD operon in a E. coli K12 ORN172 showed that YDF is important for biofilm formation but not for adherence to HeLa cells. Lastly, screening of pro-inflammatory cytokines in supernatants of Caco-2 cells infected with EAEC strains 042 and J7 and their isogenic ΔyehD mutants showed that these mutants were significantly defective in release of IL-8 and TNF-α. This study contributes to the understanding of the complex and diverse mechanisms of adherence of EAEC strains and identifies a new potential target for preventive measures of gastrointestinal illness caused by EAEC and other E. coli pathogroups.